Control of Modular Multilevel Cascade Converters for Offshore Wind Energy Generation and Transmission - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2018)
The trend of multimegawatt (Multi-MW) wind turbines, especially for offshore installations, has positioned Modular Multilevel Cascade Converters (MMCCs) as a promising solution for Wind Energy Conversion Systems (WECSs). Additionally, High Voltage Direct Current (HVDC) Transmission is likely to be the preferred option for future offshore wind farms. In both applications, Modular Multilevel Converters are an appropriate solution due to its characteristics such as high-voltage operation, controllability, redundancy, power quality and reliability. This paper presents the application of the Modular Multilevel Matrix Converter to locally interface a single wind turbine to a medium-voltage ac point of connection. Moreover, the Modular Multilevel Converter is proposed to link the wind farm to the grid onshore through an HVDC transmission line. Both converters are regulated using decoupled Vector Control Strategies. Experimental results obtained with a 27 Modular Multilevel Matrix Converter connected to a 30 power cell Back-To-Back Modular Multilevel Converter are presented to validate the effectiveness of the Proposed Control Strategies. © 2018 IEEE.